Phytotechnologies remediation of environmental contaminants - Anjum, Naser A. (CRC Press, 2013)
"Phytotechnologies: Remediation of Environmental Contaminants highlights the use of the natural-inherent traits of plants and associated bacteria and microbes to exclude, accumulate or metabolize toxic contaminants where they contribute significantly to the fate of chemical contaminants, and efficiently and sustainably decontaminate the biosphere from unwanted hazardous compounds. Written for students and researchers, it discusses recent breakthroughs in phytotechnologies, including genomics, proteomics, and metabolomics, that relate to varied environmental contaminants. The book offers an evaluation of the known plant species for their different roles in phytotechnological applications in relation to remediation of varied environmental contaminants and also explores the potential plant species from important plant families for their significance in phytotechnologies. Most importantly, it examines the physiological, biochemical, and molecular-genetic mechanisms behind the natural traits of plants and associated microbes for the accumulation, hyperaccumulation, tolerance, and remediation of varied environmental contaminants. The book provides a one-stop source of cutting-edge answers and time-saving access to the best information on the phtotechnologies and their significance for the remediation of varied environmental contaminants thus, to decontaminate the biosphere for better future"-- Provided by publisher.
Keywords: Phytoremediation.; elektronické knihy; electronic books